The Implications of the Pekanbaru–Dumai Toll Road Construction Policy on the Socio-Economic Conditions of the Communities of the Bukit Kapur District, Dumai City - Susilo Raharjo; Rendi Prayuda; Meita Istianda (Publikasi Indonesia, 2024)
The purpose of this research is to identify the influence of policy implementation on the construction of the Pekanbaru-Dumai toll road on the socio-economic conditions of the people of Bukit Kapur District, Dumai City. This research was carried out using a qualitative descriptive research method approach because this research explored the impact of toll road construction on the communities around the toll road, namely in Bukit Kapur District, where the construction of the Pekanbaru – Dumai Toll Road passes. Types and Sources of Data in this research are primary data and secondary data which include observation, non-participants, interviews and documentation. The results of the research show that the negative impact of the construction of toll roads is the use of very extensive land which will directly impact the land layout of agriculture as a whole, opening new residential and industrial areas which will directly reduce the area of agricultural land, road construction can also kill small businesses such as restaurants, grocery stores, cell phone counters and others along the Dumai - Pekanbaru highway which is now no longer the main route so they are no longer visited and the construction of toll roads hastened the demise of Pinang Kampai Dumai airport because land travel via toll roads is more efficient so now there are no more flights, while the positive impact of the construction of this toll road. The existence of toll roads will provide various conveniences, starting from cutting travel time between cities and facilitating the delivery of goods and logistics. The presence of economic opportunities for communities around the route and toll road gates so that the regional economy will grow higher so that welfare will also increase.